Genome-wide association studies for the identification of cattle susceptible and resilient to paratuberculosis - Alonso-Hearn, Marta; Badia-Bringué, Gerard; Canive, Maria (Frontiers in Veterinary Science, 2022)
Mycobacterium avium subsp. paratuberculosis (MAP) causes Johne´s disease or paratuberculosis (PTB), with important animal health and economic implications. There are no therapeutic strategies to control this disease and vaccination with inactivated vaccines is limited in many countries because it can interfere with the intradermal test used for bovine tuberculosis detection. Thus, infected animals either get culled after a positive ELISA or fecal PCR result or die due to clinical disease. In this study, we review recent studies aimed to discover genetic markers which could help to identify and select cattle less susceptible and more resilient to PTB. Recently, the genotyping and subsequent imputation to whole-genome sequence (WGS) has allowed the identification of single-nucleotide polymorphisms (SNPs), quantitative trait loci (QTL), and candidate genes in the Bos taurus genome associated with susceptibility to MAP infection. In most of these genome-wide association studies (GWAS), phenotypes were based on ante-mortem tests results including serum ELISA, milk ELISA, and detection of MAP by fecal PCR and bacteriological culture. Cattle infected with MAP display lesions with distinct severity but the associations between host genetics and PTB-associated pathology had not been explored until very recently. On the other hand, the understanding of the mechanisms and genetic loci influencing pathogen resistance and disease tolerance in asymptomatic individuals is currently very limited. The identification of long-time asymptomatic cattle able to resist the infection and/or tolerate the disease without having their health and milk production compromised is important for disease control and breeding purposes.